Differentiation of Bacillus anthracis and other Bacillus cereus group bacterial strains using multilocus sequence typing method - Graniak, Grzegorz; Olender, Alina; Naylor, Katarzyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2020)
The study describes the preparation of the phylogenetic differentiation of Bacillus cereus strains. The Bacillus cereus group of bacteria is very important for human and animal health. The multilocus sequence typing scheme has been used to present this group of bacteria’s phylogenetic relationship and structure. The MLST system was established using 60 isolates of B. anthracis, B. cereus sensu stricto, B. thuringiensis, and transitional environment strains of Bacillus spp. As a negative control, five strains of B. subtilis and B. megaterium were used. Primers for amplification and sequencing were designed to target highly conserved internal fragment of seven housekeeping genes: glpF, gmk, ilvD, pta, pur, pycA, and tpi. A total of 22 different sequence types (STs) were distinguished. Analysis of the sequence data showed that all of the Bacillus cereus strains are very closely related. The MLST scheme exhibited a high level of resolution that can be used as an excellent tool for studying the phylogenetic relationship, epidemiology, and population structure of the Bacillus cereus group strains. The MLST method additionally allows us to define the phylogenetic relationship between very closely related strains based on a combination of the sequences of all seven alleles fragments and each of them separately. Thus, this genetic investigation tool is very useful in epidemiological investigation of potential military/ bioterrorist use of B. anthracis.